Evaluation of Risk Factors and Diagnostic Methods for Cryptosporidium parvum in Neonatal Dairy Calves in Iran - Zakian, A; Rasooli, A; Nouri, M; Alborzi, A; AfsharFarnia, S; Azimpour, S; Hosseinzadeh, S; Kakolaki, MR (Journal of the Hellenic Veterinary Medical Society, 2025)
Cryptosporidium is a protozoan parasite that affects a wide range of hosts, including humans and animals. This study aimed to evaluate risk factor assessment and compare diagnostic methods for detecting Cryptosporidium parvum in neonatal Holstein calves across various farms in Iran. A total of 301 fecal samples were collected from 23 dairy farms located in six provinces. Samples were examined using immunochromatography (ICG), the modified Ziehl-Neelsen (MZN) staining method, and species-specific PCR assays. The ICG technique was performed immediately after sample collection, while the remaining samples underwent laboratory processing. The prevalence of Cryptosporidium parvum was 50.5% and 45.85% based on the MZN and ICG techniques, respectively. PCR analysis revealed a 70% positivity rate among 50 randomly selected samples. Infection rates were higher in diarrheic calves compared to non-diarrheic ones, with rates of 39.52% versus 8.55% by MZN and 41.9% versus 7.6% by ICG. Key factors influencing infection included annual rainfall, hutch hygiene, fecal consistency, and calf-cow contact. While the ICG method showed acceptable diagnostic performance in diarrheic calves, its accuracy was lower for detecting infections in non-diarrheic calves. The high prevalence of Cryptosporidium parvum among neonatal calves in Iran highlights the need for improved diagnostic and preventive measures. The ICG method can be a practical diagnostic tool but is less effective in identifying subclinical infections in non-diarrheic calves.